PROBLEMS OF THE LEARNERS’ STRESS–HANDLING IN EXTREME SITUATIONS - MKRTUMYAN , MELS; MKRTUMYAN, LILIT (Main Issues Of Pedagogy And Psychology, 2014)
The article presents the modern problems of socialization and adaptation of learners in the process of inclusive education in schools and universities of RA. The psycho–physiological mechanisms of the impact of negative factors as the major determinants of PTSD are discussed. The authors of the article propose a set of measures of psycho–hygiene and psycho–prophylaxis to ensure a high level of psychological safety and mental health of learners. A full acquisition of the complex of the psychological protection provides learners independence and autonomy in extreme situations.